EFFECT OF EMOTIONAL INTELLEGENCE AND COMPETENCE MOTIVATION AND ITS IMPACT ON PERFORMANCE LECTURE IN SINGAPERBANGSA UNIVERSITY KARAWANG - Novian Ekawati (Fakultas Ekonomi dan Bisnis, 2017)
The aim of this study was to obtain in-depth information about emotional intelligence, competence, motivation and performance. Based on the formulation of research problems that have been set, then the purpose of this study was to examine: the role of emotional intelligence in the university Singaperbangsa Karawang, the role of the competence of lecturers at the University Singaperbangsa Karawang, motivational role lecturer at the University of Singaperbangsa Karawang, role performance lecturer at the University of Singaperbangsa Karawang, role motivation to the performance professor at the University of Singaperbangsa Karawang, the relationship between emotional intelligence and competence on motivation and its impact on performance at the University Singaperbangsa Karawang.The method used is descriptive and verification methods. Population of 12060 people, a sample of 387 people using proportionate stratified random sampling technique. The analysis tool uses a range of scales, path analysis, and SPSS.The results of the study at the University Singaperbangsa Karawang show that there is a relationship between emotional intelligence (X1) and competence (X2) strongly positive (two-way). There is a partial effect of emotional intelligence (X1) on the motivation (Y). There is a partial effect of competence (X2) on the motivation (Y). There is a simultaneous effect of emotional intelligence (X1) and competence (X2) on the motivation (Y). There is the influence of motivation (Y).